Effectiveness of chlamydia Test and Treat strategy in preventing adverse pregnancy outcomes: protocol for a randomized controlled trial - Liu, Lijun; Li, Changchang; Sun, Xuewan; Yang, Bin; Zheng, Heping; Li, Meng; Huang, Shujie; Wang, Cheng; Tang, Weiming (Frontiers in Public Health, 2023)
Introduction Chlamydia trachomatis is one of the most common bacterial sexually transmitted infections worldwide, and is associated with an increased risk of adverse pregnancy outcomes. However, whether providing chlamydia screening and treatment during the first trimester of pregnancy could reduce adverse pregnancy outcomes is still not clear. This study reports a randomized controlled trial (RCT) protocol to evaluate the effectiveness of chlamydia Test and Treat during early pregnancy in preventing adverse pregnancy outcomes in China. Methods and analysis This trial is a multi-center two-arm RCT targeting 7,500 pregnant women in early pregnancy (6–20 weeks). The inclusion criteria included: 18–39 years old, on their first antenatal visit, in the first trimester, and plan to deliver in the study cities. Following a block randomization procedure, every block of twenty women will be randomly assigned in a 1:1 ratio into two arms: (1) a Test and Treat arm in which women receive free chlamydia testing immediately after enrollment and people tested as chlamydia positive will receive standardized treatment and partner treatment; (2) a control arm in which women receive regular prenatal care without receiving testing during the pregnancy period, but collect urine samples and test them after delivery or indicating a chlamydia-related complication during pregnancy happens. The primary outcome is a composite of eight adverse events rate at delivery between two arms, including stillbirth, infant death, spontaneous abortion, preterm labor, low birth weight, premature rupture of membranes, postpartum endometritis, and ectopic pregnancy. Secondary outcomes include the cost-effectiveness of the intervention, the proportion of people tested with chlamydia infection, the proportion of tested-positive patients that received treatment, and the proportion of people who were cured 1 month after the treatment initiation. Urine specimens will be collected and tested for chlamydia by using Nucleic Acid Amplification Test. Data will be analyzed according to the intention-to-treat principle. Discussion This trial will test the hypothesis that early testing and treating of chlamydia can reduce the risk for adverse pregnancy outcomes and may help in developing chlamydia screening guidelines in China and other countries with a similar prevalence of chlamydia infection. Trial registration Chinese Clinical Trials Registry, ChiCTR2000031549. Registered on April 4, 2020.